Healing veterans with video games. - Barylick, Chris
How one veteran's hospital uses video games to help treat the traumatic brain injuries of America's wounded warriors.
Keywords: Veterans; Video games; Post-traumatic stress disorder; Brain Injuries; Brain Age Rehab; Virtual Iraq